2020
DOI: 10.3390/ma13235388
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Rabbit Skin Glue to Produce Bioactive Nanofibers for Nonactive Wound Dressings

Abstract: This paper assessed the collagen glue (Col) from rabbit skin for use as a raw material in combination with different water-based dispersants of antimicrobial agents such as ZnO NPs, TiO2 NPs doped with nitrogen and Ag NPs (TiO2-N-Ag NPs), and chitosan (CS) for the production of biocompatible and antimicrobial nanofibers. The electrospun nanofibers were investigated by scanning electron microscopy (SEM), attenuated total reflectance in conjunction with Fourier-transform infrared spectroscopy (ATR-FT-IR) analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In addition, improved biological properties were also reported for alginate/nanoTiO 2 composite scaffolds, suggesting their use for tissue engineering applications [61]. In a recent study, Matei et al (2020) reported the fabrication of electrospun nanofibers based on collagen glue from rabbit skin (Col) and different antimicrobial agents, such as ZnO NPs, TiO 2 NPs doped with nitrogen, Ag NPs and chitosan (CS) in order to be used as nonactive wound dressings. In vitro cell culture tests demonstrated a concentration-dependent cytotoxicity after exposure to L929 murine fibroblasts, with Col/TiO 2 -N-Ag NPs and Col/CS formulations showing a good biocompatibility on the entire range of tested concentrations (100-1000 µg/mL) and Col/ZnO NPs exhibiting a cytotoxic effect at concentrations higher than 500 µg/mL [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, improved biological properties were also reported for alginate/nanoTiO 2 composite scaffolds, suggesting their use for tissue engineering applications [61]. In a recent study, Matei et al (2020) reported the fabrication of electrospun nanofibers based on collagen glue from rabbit skin (Col) and different antimicrobial agents, such as ZnO NPs, TiO 2 NPs doped with nitrogen, Ag NPs and chitosan (CS) in order to be used as nonactive wound dressings. In vitro cell culture tests demonstrated a concentration-dependent cytotoxicity after exposure to L929 murine fibroblasts, with Col/TiO 2 -N-Ag NPs and Col/CS formulations showing a good biocompatibility on the entire range of tested concentrations (100-1000 µg/mL) and Col/ZnO NPs exhibiting a cytotoxic effect at concentrations higher than 500 µg/mL [45].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen glue (Col) dispersion was obtained according to our previous paper [45] by solubilization in distilled water (0.5:1 w/w) and 40% acetic acid.…”
Section: Preparing Of Electrospinning Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…High systemic biocompatibility of PEG and utilisation of biomaterials generated from ECM increase the distribution of cell growth [167]. As a result, the multifunctional wound-care material PEG-based cross-linking hydrogels with good loading components, such as cells, medicines, and peptides, are being developed [168].…”
Section: Tissue Engineering (Te)mentioning
confidence: 99%
“…The disadvantage of these traditional antimicrobial agents is related to antibiotic resistance. The alternative to topical antimicrobial agents is to develop new wound healing materials based on alginate [17], chitosan [6,18], collagen [19], nanocellulose [20], inorganic antimicrobial agents such as zinc oxide [5,21], and plant extracts [22].…”
Section: Introductionmentioning
confidence: 99%